The validity and reliability of a hydraulic resistance device for assessing resisted sprint time - Sašek, Matic; Cvjetičanin, Oskar; Šarabon, Nejc (Frontiers in Sports and Active Living, 2024)
Introduction The aim of this study was to assess the validity and reliability of a hydraulic resistance device (HRD) for monitoring sprint split times under different loads within and between sessions. Methods Three 20-m sprints with low (15 N), medium-low (40 N), medium-high (50 N), and high (130 N) HRD resistance levels (loads) were performed on two separate occasions 14 days apart. Twenty-four student athletes (24.8 ± 3.8 years) participated in the first session and 13 (24.1 ± 3.2 years) of them in the second session. Resisted sprints split times over a distance of 0–20 m (t0–5, t0–10, t0–20, t5–10, t10–15, t15–20) were measured simultaneously with magnetic incremental encoder embedded in the HRD and a system of single-beam timing gates. Results The results showed acceptable to high within session (ICC3,1 = 0.91–0.99; CV = 0.92%–3.38%) and between session (ICC3,1 = 0.82–0.99; CV = 1.62%–4.84%) reliability of HRD for measuring all split times at all loads. The minimal detectable change between sessions ranged from 3.3% at high load to 9.9% at low load. The HRD systematically underestimated timing gates times at all loads (bias = 2.01–11.08%), yet good to excellent consistency was observed between the HRD and timing gates, specifically for t0–10 and t0–20 (ICC3,k lower 95% CI = 0.84–0.99). Discussion Due to high reliability and good validity in monitoring resisted sprint times, the HRD holds potential for practical and research applications.